Sustaining green roof through maintenance practice in high rise residential building in Shah Alam / Hamnah Farohiyyah Sazali - Sazali, Hamnah Farohiyyah (Faculty Architecture, Planninng and Surveying, 2014)
Green roofs have been established for over 100 years globally and they have been become one of the key elements in urban area in the past few decades. Green roof had been implemented in residential building and act as a place for social purpose. But, to compare in Malaysia, the adaptation is still low as well as the study about green roof were few in numbers. Many scientific researches focus on its cooling performance,efficiency and survival rates of plants. This research involves discovering how the green roof was maintain in high rise residential building in Shah Alam. The goal is toward providing the effective maintenance practice of green roof. This has been done by examining the green roof through condition assessment and verbal information gained through semi-structured interview at the three chosen case studies. The case study are high-cost, high rise residential building located in Shah Alam. Upon analysing of these data, it becomes clear that green roof maintenance were carried out in two aspects, the vegetation maintenance on the green roofs and the structural maintenance of the green roof. Vegetation is the key element in installing green roofs. It also provides some factors in choosing suitable plants on rooftops, factors including species that are drought tolerant, solar radiation tolerant, and cooling ability of plants. The structure on the other hand play major role in the stability and resistance. The two element which required attention are cracks and water ponding. In addition, green roofs maintenance play a critical role in improving the green roof that will ensure the proper operation of green roof. This research recommend and highlights the importance of the revolution in the implementation of the green roof itself and on improving the maintenance practice currently done.